Flora y su influencia en la hacienda agroturística El Edén - Gavilanez Soria Andrea Estefania (2024)
The work of curricular integration focuses on the relationship between the flora and the development of the agrotourism activity of the El Edén hacienda. Through a series of methodology that brings together qualitative and quantitative analyses, to examine how the diversity and characteristics of the vegetation influence the attractiveness and sustainability of the farm. With a search for important factors such as biodiversity, the conservation of native species and the integration of ecological practices, highlighting their impact on the rural tourist experience and agricultural productivity. The curricular integration work suggests strengthening environmental management on the farm, highlighting the importance of a sustainable perspective that considers the rural natural environment to improve economic and ecological results. It is invited to consider inclusive agrarian knowledge that facilitates the active participation of the community in the management of natural resources, promoting a favorable environment for the integral growth of the farm. This approach will expand the scope of this research, allowing for a better understanding of the interaction between the natural environment and human activities in the context of education and agricultural tourism.